2018
DOI: 10.26508/lsa.201800090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of human Ero1 reveals novel regulatory mechanisms for oxidative protein folding

Abstract: This study reveals novel regulatory mechanisms for human Ero1α and Ero1β, including cooperativity for oxygen binding and complex formation with PDI via a novel mixed disulfide linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…The K m of Ero1, the ER resident sulfhydryl oxidase enzymes, was determined to be 4 μ m for yeast Ero1 and 5 μ m for mammalian Ero1‐Lα . Interestingly, a recent study showed that Ero1not only has a high affinity for molecular oxygen but also a high cooperativity of oxygen binding, whilst yeast Erv1 has no such cooperativity . Moreover, using GSH‐PDI (protein disulphide isomerase) as electron donor, a K m of 89 μ m and k cat of 0.41 s −1 for Erv1 oxidase activity was obtained, which are both clearly larger than that we obtained with GSH‐Mia40 system (89 vs 3 μ m ; 0.41 vs 0.05 s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The K m of Ero1, the ER resident sulfhydryl oxidase enzymes, was determined to be 4 μ m for yeast Ero1 and 5 μ m for mammalian Ero1‐Lα . Interestingly, a recent study showed that Ero1not only has a high affinity for molecular oxygen but also a high cooperativity of oxygen binding, whilst yeast Erv1 has no such cooperativity . Moreover, using GSH‐PDI (protein disulphide isomerase) as electron donor, a K m of 89 μ m and k cat of 0.41 s −1 for Erv1 oxidase activity was obtained, which are both clearly larger than that we obtained with GSH‐Mia40 system (89 vs 3 μ m ; 0.41 vs 0.05 s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression tests to screen for optimal conditions were carried out for the constructs in 24 deep well plates. The constructs were co-expressed together with CyDisCo components from pMJS205 [18] in up to four different E. coli strains (BL21(DE3) (from Stratagene), the Keio collection parental strain BW25113 [53], MDS42 [54] and BL21 (DE3) ∆trxA/trxC [55]), up to two different media (chemically defined [56] and terrific broth autoinduction media (Formedium) with trace elements and 0.8% glycerol and at two different temperatures (30 • C and 15 • C). All the constructs were found to be best expressed at 15 • C, in BL21(DE3) cells.…”
Section: Expressionmentioning
confidence: 99%
“…Human Ero1α requires high concentrations of reduced substrate PDI for redox activation as well as for catalytic turnover (12). Both events are mediated by the same molecular determinant, specifically, the protruding β-hairpin of Ero1α interacting with the hydrophobic substrate-binding site of PDI in the b' domain (11,12). Non-native proteins, such as misfolded proteins or folding intermediates, contain exposed hydrophobic amino acids which are bound by the same substratebinding site in the b' domain of PDI (19) that interacts with Ero1α.…”
Section: Non-native Proteins Inhibit Ero1α Activity and Activationmentioning
confidence: 99%
“…As an additional control, we measured similar inhibition assays replacing Ero1α with another sulfhydryl oxidase, Erv1p, capable of oxidizing PDI despite lacking the hairpin structure of Ero1α (12,26). The oxygen consumption rate was not strongly inhibited by either 17β-E2 or BPA (Fig.…”
Section: Pdi Binds Small Hydrophobic Molecules Which Inhibit the Regmentioning
confidence: 99%
See 1 more Smart Citation